Extending dynamic models of mining subsidence - Xu-gang, Lian; Jarosz, Andrew; Saavedra, Jose; Hua-yang, D. (China University Press, 2011)
The movement and deformation processes of the overburden strata and ground surface, induced by underground mining, are affected by mining method, spatial relationships, geotechnical conditions of the rock strata and time. The authors reviewed and extended an existing classical prediction model of the dynamic subsidence, and proposed potential new research avenues offered by Cellular Automata (CA) models. The Knothe's influence function model and the significance of subcritical mining geometry were analyzed. The prediction results were verified against the subsidence field survey data to assess their quality and acceptability.